Ten prominent host proteases in plant-pathogen interactions - Thomas, E; van der Hoorn, R (MDPI, 2018)
Proteases are enzymes integral to the plant immune system. Multiple aspects of defence are regulated by proteases, including the hypersensitive response, pathogen recognition, priming and peptide hormone release. These processes are regulated by unrelated proteases residing at different subcellular locations. In this review, we discuss 10 prominent plant proteases contributing to the plant immune system, highlighting the diversity of roles they perform in plant defence.